Analysis of geo-ecological factors influencing the choice of development option for the Kumzhinskoye gas condensate field - Ivan S. Rumyantsev; Marsel G. Gubaidullin (RUDN Journal of Ecology and Life Safety, 2025)
The study considers the Kumzhinskoye gas condensate field located in the northern part of the Timan-Pechora province in the Nenets Autonomous District, its level of development, environmental situation, the significance of its industrial development. Three possible variants of the field development are presented. A review and detailed analysis of geo-ecological factors influencing the choice of the option of field development is carried out. Based on the results of the analysis, the most favourable option for environmental preservation is proposed.